Trends in Juvenile Delinquency from a Criminal Psychology and Criminology Perspective - Baráth, Noémi Emőke (Magyar Rendészet, 2023)
Juvenile crime has been showing a downward trend for years both in Hungary and internationally. Despite this, many young people are still caught by the authorities. In the study, we use the analysis of Hungarian and international statistical data to see what structural changes have occurred in the structure of crime in the past period. We assume that the – temporarily – punishable deviant behaviour of the child and juvenile population, in the absence of a suitable treatment system, turns from episodic perpetration into a series of acts. We will examine how the social, economic, demographic and legislative background influences juvenile delinquency and which psychological explanations help to understand and manage the path leading to the development of the situation. It is also important to keep technological changes in mind, since there are an increasing number of juveniles among the perpetrators of cybercrimes. Data quality and statistical diversity also present challenges to researchers, we also try to synthesise these data in the article, which can provide an explanation for why other data can be found in some databases that are not in line with each other. The study partially covers the explanation of the criminological and criminal psychological reasons behind the commission of crime. The performed analysis can contribute to the more efficient functioning of the investigative authority and the welfare system dealing with juveniles, by providing a prismatic overview of the changing trends in this paper.